EU-China relations: through the narrative of China's media - Dechun Zhang (Jurnal Studi Pemerintahan, 2021)
China is the second-biggest trading partner of the European Union, and theEU is the biggest trading partner of China. Hence, China adds EU have a close relationship. In this sense, it is vital to find the media perception of the EU and the political ideology behind their relationship. However, most of the existedstudies explore China-EU relationship through their trade information, whileignore the role of Chinese media frame of EU. This study believe that China’s official media frame offer a strong evidence to understand China-EU relation- ship. This article aims to examine China’s official media perception of the EU by systematically examine the previous study. This study finds that Chinese mediaframe EU as an economic and political partner in a positive way but try to avoidmentioning the contradiction and friction, the selective negative is-sues aremainly for propaganda and conform to Chinese government atti- tude. Hence, this study discusses that Chinese official media follow the narrative ofthe Chinese government and reflect the EU-China relationship from the Chinese government perspective.